Analgesic activity of new complex compounds SnCl4 with salicyloylhydrazones of benzaldehyde and brombenzaldehyde - Prokopchuk, Elena; Aleksandrova, Alexandra; Kravchenko, Iryna (Journal of Education, Health and Sport, 2019)
The physiological role of pain helps to avoid or limit the tissue damage and therefore it provides the vital protective function. It has been previously studied, that complex compounds SnCl4 with salicyloylhydrazones of benzaldehyde and brombenzaldehyde as well as their components represent the practical interest by the manifestation of anti-inflammatory and antidepressive action. In this case the analgesic properties of the complexes themselves, as well as compounds belonging to their structure were of interest of our study. The experiments were performed on white mice. Several chemical (allyl isothiocyanate or AITC, capsaicin, formalin) and thermal effects have been chosen in this investigation for studying the analgesic activity and establishing the possible mechanisms of antinociceptive effect. The tested compounds showed a mixed type of receptor interaction using models with different types of stimulation, which allows to make conclusions about their perspective as highly effective analgesics with a complex mechanism of action.